IRAQI EFL STUDENTS' AWARENESS OF THE PRONUNCIATION OF MORPHOPHONEMIC CHANGED WORDS AT A COLLEGE LEVEL - Te'ama Al-Atabi, Faris Kadhim; Mohammed Alhusseini, Hashim Aliwy (International Journal of Research -GRANTHAALAYAH, 2018)
This study is concerned with the morphophonemic changes as one of the most common processes in the English derivation and as a problematic area for English language learners. The study aims at investigating Iraqi college students' awareness in pronouncing the morphophonemic changes of words. To achieve this aim, the study adopts a diagnostic test of two questions. It was found that Iraqi university learners are unaware of the pronunciation of morphophonemic changes as the highest rate of their incorrect responses and the students are much unawareness at the production level than the recognition level. In the light of the results, certain recommendations and suggestions have been put for further studies.